2012
DOI: 10.1590/s0104-11692012000300008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of educational intervention on the disease knowledge of diabetes mellitus patients

Abstract: Original ArticleThe prevention of diabetes and its complications is a challenge for the healthcare team. The aim of this study was to evaluate the effect of educational action on the disease knowledge of patients with type 2 diabetes. A randomized clinical trial was conducted with 62 patients registered in a service of reference in the treatment of hypertension in 2010. Data were collected through a questionnaire applied to the Intervention (IG) and Control (CG) groups at the beginning and at the end of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
17

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 13 publications
3
30
0
17
Order By: Relevance
“…7,9,10 This result can be explained by the fact that Brazilian women live longer and tend to seek health services more frequently, thus leading to a higher probability of being diagnosed with this disease. 11 The predominance of patients aged more than 61 years suggests that the prevalence of DM2 increases with age, as it has been shown in previous studies. 12 A multicenter study on the Knowledge and attitude of patients with diabetes Assunção SC, Fonseca AP, Silveira MF, Caldeira AP, Pinho L prevalence of diabetes in Brazil revealed the influence of age on this prevalence and an increase of 6.4 times in the prevalence of diabetes from the 30-to-59-year age group to the 60-to-69-year age group.…”
Section: Discussionmentioning
confidence: 54%
“…7,9,10 This result can be explained by the fact that Brazilian women live longer and tend to seek health services more frequently, thus leading to a higher probability of being diagnosed with this disease. 11 The predominance of patients aged more than 61 years suggests that the prevalence of DM2 increases with age, as it has been shown in previous studies. 12 A multicenter study on the Knowledge and attitude of patients with diabetes Assunção SC, Fonseca AP, Silveira MF, Caldeira AP, Pinho L prevalence of diabetes in Brazil revealed the influence of age on this prevalence and an increase of 6.4 times in the prevalence of diabetes from the 30-to-59-year age group to the 60-to-69-year age group.…”
Section: Discussionmentioning
confidence: 54%
“…These results are in line with other studies, where patients who attended a diabetes education program had a higher KA score and awareness of their disease. 6,7 Regarding glycosylated hemoglobin (HbAlc) and fasting blood sugar, a statistically significant improvement was found in their mean levels after application of face to face diabetic education. These results are in agreement with those reported by Ozcelik et al in 2010 7 and Sharaf in 2013 8 who reported that, HbA1c levels were significantly lower in patients who received diabetes education.…”
Section: Discussionmentioning
confidence: 99%
“…Além da predisposição genética e a presença de comorbidades, está associado a fatores de risco modificáveis, como sobrepeso, obesidade e sedentarismo (4) . Os profissionais de saúde podem ajudar os indivíduos na gestão dos fatores de risco envolvidos, instrumentalizando-os para o adequado autocuidado (5)(6) .…”
Section: Introductionunclassified
“…Isso porque o conhecimento é influenciado por características individuais, pelo significado que o indivíduo atribui à condição crônica e por suas atitudes diante dela (9) . Estudos sugerem que indivíduos com conhecimento adequado sobre DM2 conseguem melhor controle sobre a doença e, portanto, as complicações em longo prazo associadas a ela são evitadas (5,10) . No entanto, nem todos estão preparados para realizar as atividades necessárias para o bom controle da doença (11) , sendo importante que os profissinais de saúde se empenhem em favorecer o conhecimento sobre a doença e os modos de enfrentá-la.…”
Section: Introductionunclassified